Comparative transcriptome and metabolome profiling reveal molecular mechanisms underlying OsDRAP1-mediated salt tolerance in rice - Wang, Yinxiao (Sci Rep, 2021)
Integration of transcriptomics and metabolomics data can provide detailed information for better understanding the molecular mechanisms underlying salt tolerance in rice. In the present study, we report a comprehensive analysis of the transcriptome and metabolome of rice overexpressing the OsDRAP1 gene, which encodes an ERF transcription factor and was previously identified to be conferring drought tolerance. Phenotypic analysis showed that OsDRAP1 overexpression (OE) improved salt tolerance by increasing the survival rate under salt stress. OsDRAP1 affected the physiological indices such as superoxide dismutase (SOD), catalase (CAT) and malondialdehyde (MDA) to enhance redox homeostasis and membrane stability in response to salt stress. Higher basal expression of OsDRAP1 resulted in differential expression of genes that potentially function in intrinsic salt tolerance. A core set of genes with distinct functions in transcriptional regulation, organelle gene expression and ion transport were substantially up-regulated in the OE line in response to salt stress, implying their important role in OsDRAP1-mediated salt tolerance. Correspondingly, metabolome profiling detected a number of differentially metabolites in the OE line relative to the wild type under salt stress. These metabolites, including amino acids (proline, valine), organic acids (glyceric acid, phosphoenolpyruvic acid and ascorbic acid) and many secondary metabolites, accumulated to higher levels in the OE line, demonstrating their role in salt tolerance. Integration of transcriptome and metabolome analysis highlights the crucial role of amino acids and carbohydrate metabolism pathways in OsDRAP1-mediated salt tolerance.